Combining cholesterol-lowering strategies with imaging data: a visible benefit?. (March 2019) - Koenig, Wolfgang; Giovas, Periklis; Nicholls, Stephen J
Coronary artery disease is characterised by the development of atherosclerotic plaques and is associated with significant morbidity and mortality on a global level. However, many patients with atherosclerosis are asymptomatic and the prediction of acute coronary events is challenging. The role of imaging studies in characterising plaque morphology and stability is emerging as a valuable prognostic tool, while providing evidence for the beneficial effects of cholesterol-lowering therapy on plaque burden. This review provides an overview of contemporary studies describing the value of imaging strategies for atherosclerotic plaques. Coronary angiography is commonly used in the clinical setting, but requires a significant radiation dose (similar to computed tomography). Magnetic resonance imaging evaluation of coronary vessels would avoid exposure to ionising radiation, but is not yet feasible due to motion artefacts. The roles of alternative imaging techniques, including grey-scale intravascular ultrasound, optical coherence tomography and near-infrared spectroscopy have emerged in recent years. In particular, grey-scale intravascular ultrasound has been effectively applied to detect changes in plaque burden and features of plaques predictive of rupture, as well as plaque characteristics during cholesterol-lowering therapy, providing novel insights into factors that may contribute to treatment effectiveness. Challenges and limitations to the use of imaging techniques are considered in this context, along with future imaging strategies.